The expression which you said is right sir.... wkt, R1R3=R2R4 From this we can calculate the value of R2, so R2=R1R3/R4 if we substitute this value in our expression R1/R1+R2 =R4/R3+R4, then R1/R1+R2= R1/R1+(R1R3/R4) =R1/((R1R4+R1R3)/R4) =R1R4/(R1R4+R1R3) cancelling the like terms i.e R1 we get =R4/R4+R3 Hence proved
The expression which you said is right sir....
wkt, R1R3=R2R4
From this we can calculate the value of R2, so R2=R1R3/R4
if we substitute this value in our expression R1/R1+R2 =R4/R3+R4, then
R1/R1+R2= R1/R1+(R1R3/R4)
=R1/((R1R4+R1R3)/R4)
=R1R4/(R1R4+R1R3)
cancelling the like terms i.e R1 we get
=R4/R4+R3
Hence proved
Nuvu kuda UA-cam channel Petey bro
thank you for this explanation sir!!!! it is awesome
You are the best brother... Keep moving
Thank you so much 😀
A clear explanation.. good
Good going sir..keep it up
👏👏👏👍👏👏👏
Nice explanation sir
Good explanation
It would be more easy to understand if you give some values and solve it because of only R1,R2 it is being more complicated
Nice
👌👌👌
Tq. Keep supporting plz 🙏
Hi sir....following ur lectures can you start pdc also simultaneously ur lectures easy to learn
Automation in digital instruments.. like auto ranging auto polarity indication n zeroing. Sir..
Hi sir....following ur lectures can you start pdc also simultaneously ur lectures easy to learn